Diagnostic Efficacy of Cone Beam Computed Tomography Sialography (Sialo-CBCT) in Salivary Gland Pathologies: A Systematic Review - Sivadas, Smrithy K.; Hegde, Shruthi; Ajila, Vidya; Tannishtha (Indian Journal of Radiology and Imaging, 2025)
This article aims to investigate the clinical usefulness of sialography with cone beam computed tomography (CBCT), also known as Sialo-CBCT, for the diagnosis of salivary gland diseases.Literature search was performed in PubMed and Web of Science databases with search terminologies “sialography, cone beam computed tomography sialography, salivary gland diseases.” Thirteen articles that examined the diagnostic potential of Sialo-CBCT were included in the present review. The search complied with PRISMA criteria, and the protocol was registered in the PROSPERO [CRD42024503038].Out of thirteen publications included in the review, three were studies that optimized the effective dosage and image quality in Sialo-CBCT and ten remaining included imaging performed in patients with salivary gland diseases.The findings suggest that 3D CBCT combined with sialography has good diagnostic potential in visualizing the ductal subdivisions and anatomy of the salivary glands as well as the identification of salivary gland pathologies. Characteristic features of imaging modalities such as plain radiography, ultrasonography, CT-sialography, MR-sialography, and CBCT-sialography were outlined in the review.
Keywords: sialography; salivary gland diseases; cone beam computed tomography